Training Assessment Project : Moldova - World Bank Group (World Bank, Washington, DC, 2019)
Moldova, like many other countries in the region, is facing rapid economic and demographic transitions. Employers report that inadequate levels of workforce skills hamper their productivity. Recognizing the importance of workforce development to improve the country’s socioeconomic prospects, the Government of Moldova approved the educational development strategies for 2013-2020. The main objectives are to improve the quality of education and training system and better match its outcome with the labor market needs. In particular, information on short-term training providers, including their characteristics, practices, and outcomes, are not available. Given this lack of information and the government’s strong interest in better understanding specifically the provision of short-term training providers, the World Bank launched the Training Assessment Project (TAP) to identify the landscape and characteristics of these institutions and assess the extent to which they follow practices that are conducive to improved service delivery. TAP collects data on the outcomes of training institutions as an indicator of their performance. To get an accurate picture of the characteristics, actions, values, and outcomes of training providers, TAP uses two types of data collection instruments - a questionnaire for training institutions and complementary focus group guides to gather qualitative data on the same topic matters from students, graduates, and employers. This report will present findings from the data collected on short-term training providers in Moldova in 2017-2018. The report intends to inform both short-term training providers and the state entities responsible for the governance of these institutions.